P-BN50 Transcystic CBD Exploration: The First-Line Treatment of CBD Stone - A Single Centre 12-month Review of Practice. (16th December 2021) - Rossborough, Catherine; Mackey, Rebecca; McCain, Scott; Gray, Ronan; Spence, Gary
Abstract: Background: In the UK around 15% of the population will have gallstones and as such biliary pathology makes up a significant proportion of emergency and elective general surgical practice. Within this 10% will have choledocholithiasis; the management of which remains widely varied.   A single-stage laparoscopic cholecystectomy with transcystic common bile duct exploration has been shown to be a safe and efficient option avoiding a choledochotomy and risks associated with ERCP. The aim of this study was a 12-month review of data following the adoption of this approach; assuming that laparoscopic transcystic CBD exploration was the ideal treatment for CBD stones. Methods: This was a retrospective, single-centre, observational study. All patients who underwent a laparoscopic transcystic CBD exploration from June 2020 to June 2021 were included both in the elective and emergency setting. Patient demographics were varied with ages ranging from 15 to 76 and ASA classification of 1 -3, showing a significant proportion with comorbidities.  Data collection was done through a review of a contemporaneous operative database and a follow-up morbidity period of 30 days was cross-referenced with electronic healthcare records.  The primary outcome studied was CBD stone clearance. With secondary outcomes measures including complications, length of stay and the role of preoperative imaging versus intraoperative cholangiogram.  Results: A total of 49 patients were included within the study, of which 61% were emergency. The primary outcome of CBD stone clearance was achieved in all elective patients with one emergency patient requiring ERCP for a retained fragment at day 8.  There were no other complications in the remaining 48 patients, making the 30-day morbidity 2% upon review of electronic care records. One patient was converted to open due to concern with regards to potential CBD injury but this was demonstrated not to be the case. The median duration of hospital admission was 3 days with a range from 0- 15, with the median stay for elective cases being 1 day. Finally, 39 patients underwent intraoperative cholangiograms prior to duct exploration as a means of identifying CBD calculi and delineating anatomy. Those 10 that did not; all had an MRCP within 30 days of surgery demonstrating CBD calculi and as such proceeded straight to CBD exploration. Conclusions: Laparoscopic cholecystectomy and transcystic CBD exploration, with adequate training and exposure, is a viable and safe first-line approach for all cases of choledocholithiasis both in the elective and emergency setting; demonstrating advantages by avoiding additional procedures thereby reducing costs, inpatient bed days and a risk of further complications and being truly minimally invasive.  The principal findings of this study were that the transcystic CBD exploration route can achieve successful CBD stone clearance rates in close to 98 per cent of patients with a low morbidity rate, and a short median length of hospital stay. This study of course has several potential limitations; given it was a retrospective single-centre observational study there is likely a degree of selection bias and although follow up was complete in all patients to 30 days via electronic care record it was not routine practice to offer face to face follow up given the low incidence of delayed complications. On the basis of this review, the transcystic approach has become the primary strategy for patients with common bile duct stones within this unit.